Study Of The Heritage Of Imam Mаturidi At The Imam Mаturidi International Scientific Research Center: Analysis And Prospective Plans (The Journal of Interdisciplinary Human Studies, 2026)
This article presents the work carried out at the Imam Maturidi International Scientific Research Center on studying, critically editing, translating, and disseminating the heritage of Imam Abu Mansur al-Maturidi. It describes the establishment of the Center, its collection of manuscript copies of “Kitab al-Tawhid” and “Ta’wilat al-Qur’an” from libraries in Uzbekistan, Turkey, the Arab world, and Europe, and the methodology used to prepare the new critical edition of “Kitab al-Tawhid” (presented at the 2024 Cairo International Book Fair) and the ongoing Uzbek translation of “Ta’wilat al-Qur’an.” It also outlines the Center’s prospective plans for further manuscript research.
Keywords: Imam Maturidi; Imam Maturidi International Scientific Research Center; Kitab al-Tawhid; Ta’wilat al-Qur’an; manuscript; critical edition; Maturidism; kalam; textual criticism; Uzbekistan